Community–based adaptation to climate change: A theoretical framework, overview of key issues and discussion of gender differentiated priorities and participation - Bryan, Elizabeth; Behrman, Julia A. (International Food Policy Research Institute, 2013)
This paper provides a comprehensive overview of the fundamentals of community–based adaptation (CBA) efforts. To start, it develops and describes a framework on adaptation to climate change used as the basis for this research. The paper then defines the characteristics or principles of CBA and describes why it is an essential part of the adaptation process. Following this, it identifies the limitations of or constraints to CBA in practice, including the need to link CBA to the larger adaptation and development processes and discusses institutional arrangements for CBA.